Good-bye Stacey, good-bye - Epstein, Gabriela; Lamb, Braden; Martin, Ann M., 1955- (New York : Graphix, an imprint of Scholastic, 2022)
"Stacey McGill is moving back to New York! That means no more Stoneybrook Middle School, no more Charlotte Johanssen, and worst of all... no more Baby-sitters Club. Stacey's friends are crushed when they hear that Stacey's moving, especially Claudia. Stacey was her first best friend. What kind of going-away present is good enough for someone so special? How will the BSC go on without Stacey?"--
2.7
4-7
GN340L
GN340L
Accelerated Reader AR
Keywords: Babysitters Club (Imaginary organization) -- Comic books, strips, etc. -- Juvenile fiction; Babysiting -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Moving, Household -- Comic books, strips, etc. -- Juvenile fiction; Babysitters Club (Imaginary organization) -- Fiction; Babysiting -- Fiction; Friendship -- Fiction; Moving, Household -- Fiction; Babysitters Club (Imaginary organization) -- Fiction; Babysiting -- Fiction; Friendship -- Fiction; Moving -- Fiction